2017
DOI: 10.1038/srep41711
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic properties of Scutellaria baicalensis in db/db mice evaluated using Connectivity Map and network pharmacology

Abstract: We have reported that an extract of Scutellaria baicalensis (ESB) has effects against obesity and hypertriglyceridemia in type 2 diabetic animal model (db/db mouse). In the present study, we tried to explain the pharmacological effects of ESB by integrating gene expression information from db/db mouse liver with that of ESB-treated HepG2 hepatocellular carcinoma cells. Using Connectivity Map (cmap) analysis, we found an inverse relationship in the pharmaceutical profiles based on gene expression between db/db … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…In accordance with the results of the direct measurement of pathway activity, upregulated and downregulated AD genes showed reciprocal associations with signaling pathways (pathway clusters 1 and 6) and metabolism pathways (pathway cluster 3), respectively. We reported previously the reciprocal regulation of biological functions between signaling pathways and metabolic pathways in diverse biological situations [ 15 , 17 , 18 ] which suggests that the reciprocal regulation of gene expression and biological functions may be the global regulatory mechanism that is predetermined in the promoter sequences of genes. Protein modification such as glycosylation, acetylation, and phosphorylation is also thought to play an important role in the reciprocal regulation of metabolism and signaling processes [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In accordance with the results of the direct measurement of pathway activity, upregulated and downregulated AD genes showed reciprocal associations with signaling pathways (pathway clusters 1 and 6) and metabolism pathways (pathway cluster 3), respectively. We reported previously the reciprocal regulation of biological functions between signaling pathways and metabolic pathways in diverse biological situations [ 15 , 17 , 18 ] which suggests that the reciprocal regulation of gene expression and biological functions may be the global regulatory mechanism that is predetermined in the promoter sequences of genes. Protein modification such as glycosylation, acetylation, and phosphorylation is also thought to play an important role in the reciprocal regulation of metabolism and signaling processes [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Probes on arrays with signal intensities that were 1.4-fold higher than the local background were selected exclusively, as described previously [ 17 , 18 ], and were then normalized using the quantile method, which can adjust the variability within and between samples [ 19 ]. Hierarchical clustering based on the expression levels of genes was performed using the Gene Cluster 3.0 program and visualized using the Java TreeView program [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…pathway activity. As a measure of pathway activity, the expression values of genes included in the pathway were used as previously reported by us 29,30,50 . In brief, for each pathway, the log-transformed values of expression ratios of genes compared to the control were added linearly.…”
Section: Measurement Of Similarity Between Therapeutic Profiles Simimentioning
confidence: 99%
“…In recent years, many herbal medicine studies applied network-based approaches to overcome the lack of information on the targets of the identified herbal constituents 27,28 . We also reported that combining omics and pharmacogenomics network approaches can reveal the therapeutic properties of herbal drugs 29,30 . However, unfortunately, most network-based studies of herbal drugs are based on limited experimental evidence that does not fully reflect the diverse aspects of the disease.…”
mentioning
confidence: 97%